Aerodynamic parameters of windbreak based on its optical porosity - STŘEDOVÁ, Hana; PODHRÁZSKÁ, Jana; LITSCHMANN, Tomáš; STŘEDA, Tomáš; ROŽNOVSKÝ, Jaroslav (Contributions to Geophysics and Geodesy, 2012)
The paper summarizes the results of wind velocity measurement in different distances from windbreak in combination with optical porosity (OP) determination in different periods. Experimental data were obtained by direct measurement of wind speed and OP analyses of images of four windbreaks in Southern Moravia (part of Czech Republic). Wind speed at 2 m above the soil surface in a defined distance from windbreak had been measured since 2006. Thirty images of different phenological stages of selected windbreaks from 2006 to 2010 were analyzed. Windward or leeward images were converted into black and white spectrum. All available measurements were used for a map creation. The highest values of OP (up to 50%) are achieved in non-vegetation period. Due to the high OP variability in height of terminal tree branches “OP reduced” was also assessed (just squares to 2/3 height of windbreaks were evaluated). The wind speed reduction on the leeward side relatively strongly correlated with OP value. The highest correlation was found out when the wind speed measurement at 50 m on leeward side was used. The dependence decreases with increasing distance. Full foliage in summer (10% OP) reduces a wind speed about 60% at 50 m and about 30% at 150 m on the leeward. These values for non-foliaged windbreaks decrease to 80 and 90%. Maximum distance of windbreak effect on wind speed reduction was found out by the extrapolation of the curves constructed using the regression equation of wind speed reduction in dependence on OP and different distances from the windbreak. Regardless of OP value, the reduction effect disappears at a distance of 250 m. The quietest zone of evaluated windbreak with an average height of windbreaks 15–18 m was detected in the area about four times the height (4H). The effect of windbreaks decreases with increasing porosity.